Giant idiopathic pyoderma gangrenosum at an unusual site with highly elevated c-ANCA levels: A rare association - Lovleen Kaur; Mohita Mahajan; Parul Chojer; Bharat Bhushan Mahajan; Suresh Kumar Malhotral (Our Dermatology Online, 2021)
Pyoderma gangrenosum (PG) is a rare neutrophilic disorder with an incidence rate of 3-10 cases per million per year, characterized by classically painful and aseptic ulcers, which may be associated with underlying systemic diseases. The pathergy reaction is seen in one-fourth of patients with PG. Accurate and timely diagnosis is crucial, as PG is known for its rapid progression. The management of PG is challenging and depends on its severity and rate of progression. An underlying systemic involvement should be sought even in spite of no symptoms. Herein, we report a case of giant pyoderma gangrenosum involving almost the entire left buttock with exceptionally raised c-ANCA levels, but no underlying systemic abnormality. The patient reported intense pain, rapid progression of the ulcers, an inability to perform daily activities, was significantly morbid and pathergy-positive. Aggressive and early management is required in cases such as this. A dramatic response was achieved with a combination of cyclosporine, dapsone, and methylprednisolone pulses.